Se da expresia E(x)=(1/x-2 - 2/x + 1/x+2 ) :4 /x(x la a 2-a - 4)
Aratati ca E(x)=2
Răspunsuri la întrebare
Răspuns de
0
E(X) = (1/X-2 - 2/X + 1/X+2) : 4/X(X^2 - 4)
E(X) = [X(X+2) - 2(X^2-4) +X(X-2)]/X(X-2)(X+2) : 4/X(X-2)(X+2)
E(X) = (X^2+2X-2X^2+8 + X^2-2X)/X(X-2)(X+2) × X(X-2)(X+2)/4
E(X) = 8/4
E(X) = 2
E(X) = [X(X+2) - 2(X^2-4) +X(X-2)]/X(X-2)(X+2) : 4/X(X-2)(X+2)
E(X) = (X^2+2X-2X^2+8 + X^2-2X)/X(X-2)(X+2) × X(X-2)(X+2)/4
E(X) = 8/4
E(X) = 2
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă